A child with myoclonus-dystonia (DYT11) misdiagnosed as atypical opsoclonus myoclonus syndrome. (November 2015) - Drivenes, Bergitte; Born, Alfred Peter; Ek, Jakob; Dunoe, Morten; Uldall, Peter Vilhelm
Abstract Introduction DYT11 is an autosomal dominant inherited movement disorder characterized by myoclonus and dystonia. Clinical presentation We present a case with atypical symptoms and with episodes of ataxia and myoclonus preceded by infections. Atypical presentation of opsoclonus myoclonus syndrome was suspected and treatment with bolus steroids and immunoglobulin were initiated with some response over 28 months. A re-evaluation gave suspicion of a dyskinetic disorder and whole exome-sequencing was performed but no causal variant was identified. Outcome A specific analysis of the SGCE gene was subsequently initiated, which revealed a pathogenic aberration confirming the diagnosis of DYT11. Conclusion A clinical DYT11 diagnosis can be difficult to establish in early childhood without a known family history.